XIV International Symposium on Antarctic Earth Sciences: a holistic view of the white continent - Carrasco Cerda, Jorge Fernando; Casassa, Gino (My University, 2025)
In February 2024, central Chile experienced one of the deadliest wildfire disasters in its history, with over 136 fatalities, thousands of homes destroyed, and extensive environmental damage. This paper analyzes the contributing factors, impacts, and lessons from the Valparaíso mega-fire, situating it within broader climatic, ecological, and governance contexts. Global warming has increased the frequency and severity of extreme weather events, including heat waves and droughts. Chile is not immune to the increase in these extreme events. In addition, the El Niño episode amplified natural atmospheric variations, leading to warmer-than-usual conditions during the summer, which happened with the 2023-2024 El Niño when the mega-fire took place on February 2-4, 2024. The meteorological factors leading to the heat wave event and the favorable conditions for spreading forest fires (the 30-30-30 rule) were accurately forecast five days before, providing early warnings. Despite significant advancements in early warning systems and emergency alerts, the response to the 2024 fire revealed critical limitations in preparedness, particularly in wildland-urban interface areas. This event shows the vital need for proactive fire-forest management from the high-level authorities to residents to minimize its i mpact and to adapt strategies to address the growing threat of climate-induced wildfires.
Keywords: antarctic earth sciences; ice-sheet dynamics; tectonics and geophysics; remote sensing and emerging technologies; paleoclimate and global climate interactions